HMI'S ROLE IN ADVOCACY ON NATIONAL ISSUES: A REVIEW OF ACTIVISM AND PUBLIC COMMUNICATION - Julpahri Tanjung; M. Yoserizal Saragih (Journal Analytica Islamica, 2025)
This study examines the role of the Islamic Students Association (HMI) in advocating for national issues through the perspectives of student activism and public communication. As a student organization with a long history in Indonesia's socio-political movements, HMI plays a strategic role in shaping public opinion and promoting policy change. Using a qualitative approach and case study method, this study examines the dynamics of the HMI movement in responding to national issues such as democracy, social justice, and freedom of expression. Data were obtained through documentation of activities, observation of official social media, and analysis of mass media reporting on HMI actions. The primary focus of the analysis was directed at activism patterns, public communication strategies, and the resulting media narratives. The findings indicate that the success of HMI's advocacy is influenced by its ability to contextually articulate issues, build strategic communication networks with the media, and integrate Islamic values as the moral foundation of the movement. Furthermore, the use of social media is an important instrument in disseminating messages and mobilizing public support. This study strengthens understanding of the relationship between student movements, political communication, and public relations strategies in a democratic space. It also offers practical recommendations for HMI to develop a communication approach that is adaptive to social and technological change. Thus, HMI's role in advocating national issues is understood not only as a response to the political situation, but as an effort to build a structured and sustainable national discourse.